Analysis of climate change in a high andean ecosystem, riobamba-ecuador - Pérez, Natalia Alexandra (2020)
The purpose of this research is to demonstrate the existence of climate change in a high Andean ecosystem of Ecuador, through the study of the linear trend of the maximum, minimum, average and precipitation temperature of the meteorological station (M1036) of the Instituto Nacional de Meteorología e Hidrología (INAMHI) located in the Escuela Superior Politécnica de Chimborazo (ESPOCH).  The univariate statistical analysis of the multiyear monthly averages of the years 1976 to 2017 determined a dry climate in the months of June to September and a humid climate in two intervals (February - May and October - December). On the other hand, by means of the Mann Kendall Test, it was evidenced that the average temperature showed a decreasing tendency (-0.004); while the maximum, minimum and precipitation temperature had an increasing tendency (0.0002, 0.003, and 0.039 respectively), where the last two are significant at 5%. It is concluded that climate change is plausible in the central andean area of Ecuador, generating environmental  problems that we must face, and that public policy articulators in the country should consider as inputs for planning.